French and Italian names of colour shades in fashion discourse – a comparative analysis - Antoniewska-Lajus, Dorota; Skuza, Sylwia (Papers in Linguistics, 2023)
The article is part of the research on chromatic vocabulary from a comparative perspective and its aim is to analyse the contemporary names of shades (understood as hyponyms of basic colour names) in Italian and French used in press texts on fashion. The authors refer to the concept of basic colour names (Berlin, Kay 1969), reference names, works in the field of colour semantics and cognitive linguistics. Names of shades excerpted from the body of linguistic material were subjected to preliminary morphological analysis, and then the way of colour conceptualisation was examined by determining the dominant lexical fields created by reference nouns, as well as scrutinising adjectives which define colours. The conducted analysis showed similarities between both languages in the structure of shade naming (with a clear preference for reference names) and the selection of referents. It also indicated that there can be noticed unification of chromatic language due to influences of English. What is more, results showed a connection of the scrutinised vocabulary with a given socioculture and incongruence of seemingly equivalent concepts. The scrutiny of neologisms demonstrated the importance of meanings at the level of connotations, and proved the need for in-depth research on the semantics of the contemporary shade vocabulary.